KOMUNIKASI, MOTIVASI, DISIPLIN DAN KINERJA KARYAWAN UNIVERSITAS SWASTA DI MADURA - Sayyida Sayyida; Alwiyah Alwiyah (Fakultas Ekonomi dan Bisnis, 2018)
Good employee performance is the expectation of Wiraraja University Sumenep.Many factors that affect the performance of employees such as communication,motivation, and discipline. This study aims to analyze the influence of communication(vertical and horizontal), motivation (financial and nonfinancial) and work discipline ofemployee performance at Wiraraja University. Wiraraja University has 99 administrativeemployees. Data obtained through a questionnaire distributed to University employees. Avalid questionnaire that can be analyzed a number of 55 questionnaires. Validity andreliability tests are used to ensure that the data obtained come from a valid and reliablequestionnaire. Descriptive analysis is used to give an overview of the data. Correlationanalysis followed by logistic regression analysis to model the influence ofcommunication, motivation and work discipline on employee performance. The results ofthis study indicate that only financial motivations that affect to performance. Althoughdescriptive overview of data shows that the majority of employees have goodcommunication skills, good motivation and good performance but only financialmotivation that have significantly affect to the performance of employees at WirarajaUniversity. This results is expected to be the foundations of making policies leadership inWiraraja University that related with employee performance.